Estudo terapêutico comparativo entre fluconazol e itraconazol na esporotricose felina - Santos, Amanda Maria Miranda Rodrigues dos (2021)
Due to reports of refractoriness and therapeutic failure of itraconazole in feline sporotrichosis, fluconazole appears as a therapeutic option. The objective was to carry out a comparative therapeutic study between fluconazole and itraconazole, regarding efficacy, safety and treatment time until discharge, for use in feline sporotrichosis. Thus, 20 cats with sporotrichosis were randomly divided into two groups: GI (treatment with itraconazole, n = 10) and GF (treatment with fluconazole, n = 10). The drug capsules were administered daily, at a dose of 25 to 100mg per weight range. The therapeutic evolution was followed for 210 days, through reduction of the main lesion and/or regression or opening of the lesion in the nostril (efficacy of the drug); treatment safety, with fortnightly clinical evaluations (clinical parameters, adverse reactions, evolution of dermatological lesions, respiratory signs) and laboratory evaluations (blood count and serum biochemistry), and time for medical discharge. The average time of treatment in the FG was 23.5 weeks, with four medical discharges, two deaths, one dropout and three treatment failures; and in GI it was 19.7 weeks, with four medical discharges, three deaths, two dropouts and one treatment failure. Both GF and GI showed no changes in clinical and hematological parameters. There was a 59% reduction in the size of dermatological lesions in the FG and 94.67% in the GI, while all obstructive lesions in the nasal cavity regressed in both groups. In GI, ALT (15th day of treatment) and AF (15th and 75th day of treatment) increased significantly. In FG, PA increased significantly (135th day of treatment) compared to days 0 and 15 of the study, PPT at 75 and 105 days of treatment, while globulins on day 105. The use of fluconazole and itraconazole demonstrated safety and efficacy in the treatment of feline sporotrichosis, with fewer adverse reactions to fluconazole, while the IG was discharged before the FG and, at the clinical level, itraconazole stands out as a therapeutic option.